LITERATURE REVIEW BENEFITS OF LEAN MANUFACTURING ON INDUSTRY PERFORMANCE AND PROPOSED IMPLEMENTATION IN MANUFACTURING - Adam Maulana Irfan; Ade Setiawan; Anggit Nur Fauzy; Muslihun, Muslihun; Yudi Prastyo (Journal of Management and Innovation Entrepreneurship (JMIE), 2025)
This study aims to analyse the benefits of implementing the Lean Manufacturing concept in improving the performance and competitiveness of the manufacturing industry, as well as to propose strategies for its effective implementation. The research method used is a qualitative literature review, by collecting, analysing, and synthesising findings from 20 journal articles published between 2020 and 2025 that discuss Lean Manufacturing practices in various industrial sectors. The research results show that the application of Lean Manufacturing provides significant benefits, including reducing waste (muda), increasing production efficiency, improving product quality, and enhancing customer satisfaction. In addition, the integration of Lean principles with digital technologies in the Industry 4.0 era—known as Lean 4.0—has been shown to increase operational flexibility, process automation, and real-time decision-making capabilities. However, several challenges such as limited lean culture, lack of management commitment, and employee resistance remain obstacles to sustainable implementation. The conclusion of this study states that Lean Manufacturing is an effective strategic approach for improving industrial performance and competitiveness when supported by strong organizational commitment and continuous improvement culture.